The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5334/aogh.2617
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Exposure to Lead-Containing Welding Fumes and the Levels of Reproductive Hormones

Abstract: Background:Inhalation of lead oxide fumes may cause lead poisoning. Lead has been proven to have harmful effects on different organs. This study aimed to investigate the relationship between the concentration of lead fumes and the levels of reproductive hormones among exposed welders.Methods:A total number of 165 individuals of a construction industry of water pipelines, including 85 welders as the exposure group and 80 administrative staff as the non-exposure group were selected for study. The National Instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…The findings of the current study were also consistent with those of Dehghan et al (2019), who investigated the relationship between exposure to lead-containing welding fumes and the levels of reproductive hormones. They discovered that the blood lead concentration was much greater than the biological exposure index (BEI) advised by the American Conference of Governmental Industrial Hygienists (ACGIH) (p< 0.05).…”
Section: Discussionsupporting
confidence: 91%
“…The findings of the current study were also consistent with those of Dehghan et al (2019), who investigated the relationship between exposure to lead-containing welding fumes and the levels of reproductive hormones. They discovered that the blood lead concentration was much greater than the biological exposure index (BEI) advised by the American Conference of Governmental Industrial Hygienists (ACGIH) (p< 0.05).…”
Section: Discussionsupporting
confidence: 91%
“…In males, optimal levels of testosterone exert anti-inflammatory activity by inhibiting the upregulation of pro-inflammatory cytokines and promoting the expression and activities of anti-inflammatory cytokines [ 72 ], thus preventing inflammation-induced oxidative stress [ 68 , 73 ]. The observed decline in testosterone in lead-exposed rats aligns with and forms an extension of previous human and animal studies [ 74 , 75 ] that observed a decline in circulating testosterone levels following lead exposure. The present findings suggest that lead-induced suppression of circulating testosterone promotes the upregulation of pro-inflammatory cytokines and activation of oxidative stress cascades, resulting in endothelial dysfunction and reduced erectile function.…”
Section: Discussionsupporting
confidence: 88%
“…The results of these studies is consistent with the results of the current study. On the other hand, a cross-sectional study was done by Dehghan et al 9 , (2019) to investigate the association between BLC and ALC with reproductive hormones of 85 welders working in a water transfer company in Iran. It was found that the mean BLC among welders was 460.28 ± 93.65 μg/L which was significantly higher than the permissible limit.…”
Section: Discussionmentioning
confidence: 99%
“…About 11 million people work as welders in the world; besides, 110 million people are continuously exposed to various levels of welding fumes released during welding process at work. The welding fumes are aerosols consisting of different metals such as lead, ferrous, copper, nickel, magnesium, zinc, cobalt, cadmium, titanium, etc 8,9 . Lead intoxication could be either acute or chronic.…”
Section: Introductionmentioning
confidence: 99%